PEMBERIAN KOMPOS KULIT BUAH KAKAO DAN AIR KELAPA TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Yassi Oviana Putri; Islan ' '; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research is to find out the interaction of cocoa pods compost (KKBK) and coconut water as well as finding the best dosage of compost and the best concentration of coconut water of chose on the growth of cocoa seedling (Theobroma cacao L.). This research used Completely Randomized Design (CRD) with two factors. First factor is the dosage of cocoa pods compost which 4 levels. Second factor is the concentration of coconut water which 3 levels. The combination of these two factors become 12 treatmens and with 3 replication there are 36 experimental units. Each experimental units 2 seedlings so that there 72 seedlings. Parameters observed are seedling height, stem diameter, number of leafs and leaf area. Analysis used Analysis of Variance and further by Duncan New Multiple Range Test (DNMRT) at 5 % level. The result of the research shows that combination of KKBK application and coconut water has no effect to all parameters. The combination of KKBK with dosage of 210 g/plant and the concentration of coconut water of 75 % trend to increase seedling height and stem diameter of cocoa seedling. The application of KKBK with 210 g/plant dosage has good effect on seedling height, stem diameter, number of leaf, and leaf area. The application of coconut water with 75 % concentration has good effect on stem diameter and  number of leaf,  and with 100 % concentration has good effect on seedling height and leaf area.   Keywords : cocoa, compost, cocoa pods compost, coconut water